(untitled) (Research, Society and Development, 2020)
Psychrotrophic microorganisms, especially Pseudomonas spp., are present in the microbiota of refrigerated milk as they can grow at refrigeration temperatures irrespective of their optimal growth temperature. Psychrotrophic counts ranging from 105 to 108 CFU/mL in refrigerated raw milk effect cheese quality, since the synthesized thermoresistant enzymes affect the nutritional value, sensory properties, and texture. Cheese is the dairy product with the highest growth rate in the food industry in Brazil in recent years and meets the current consumption trends of nutritious and practical foods. The objective of this review was to address the importance and influence of the psychrotrophic raw milk microbiota on the quality and sensory properties of cheese. The enzymes produced by psychrotrophic microorganisms lead to taste changes, undesirable clotting times, increased concentrations of free fatty acids and free amino acids, and a reduced shelf-life, in addition to negatively affecting cheese yields. Proteases from psychrotrophs are also associated with slicing problems and progressive loss of the elasticity of cheese, a bitter taste, and increased clotting times of cheese produced with pasteurized milk. On the other hand, their lipases increase the clotting time and have a negative effect on the sensory properties by providing a rancid, soap, metallic, or oxidized smell and taste. The control of the psychrotrophic population found in refrigerated raw milk contributes to better cheese production yields and desirable texture and sensory properties, which extends the shelf-life of cheese and improves consumer acceptance.